Cuidados de enfermería en un paciente con restauración de tránsito intestinal por accidente automovilístico - Collantes Ramirez, Jeniffer Edith (2024)
Intestinal transit restoration refers to a surgical procedure performed when a person has suffered serious injuries to the intestine as a result of a traffic accident.Therefore, this case study focused on analyzing the nursing care provided to a 40-year-old patient who underwent surgery to restore intestinal transit after a previous colostomy due to a car accident. Interventions were implemented according to North American Nursing Diagnosis (NANDA), Nursing Outcomes Classification (NOC outcomes), and Nursing Interventions Classification (NIC interventions), including postoperative pain management, fall prevention, and infection risk control. the surgical wound. Despite the very delicate clinical condition, the surgical interventions and nursing care were decisive for postoperative recovery and satisfactory medical discharge. During the diagnosis and planning of the care plan, the importance of holistic evaluation and adaptation of pain management strategies was highlighted, as well as the need to educate the patient about preventing falls and maintaining aseptic practices to prevent healthcare-associated infections (HAI). This case has significant implications for clinical practice in nursing and since it allows us to recognize those practices that are essential for a successful recovery. These findings can serve as a guide for future cases and contribute to the continuous improvement of the quality of nursing care in surgical settings.